2017
DOI: 10.3389/fpsyg.2017.01205
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical Role Parallelism Influences Ambiguous Pronoun Resolution in German

Abstract: Previous research on pronoun resolution in German revealed that personal pronouns in German tend to refer to the subject or topic antecedents, however, these results are based on studies involving subject personal pronouns. We report a visual world eye-tracking study that investigated the impact of the word order and grammatical role parallelism on the online comprehension of pronouns in German-speaking adults. Word order of the antecedents and parallelism by the grammatical role of the anaphor was modified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 42 publications
0
14
3
Order By: Relevance
“…The results of Experiments 1a and 2a indicate that after encountering the object pronoun, L1 and L2 German speakers did not show a rapid use of grammatical role parallelism. L1 participants did not reveal any preferentially looks towards the object antecedent, which is not in agreement with previous studies (e.g., Sauermann, Gagarina 2017, Smyth 1994, Schumacher et al 2016. Whereas L2 participants looked more frequently towards the object antecedent than to the subject antecedent.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The results of Experiments 1a and 2a indicate that after encountering the object pronoun, L1 and L2 German speakers did not show a rapid use of grammatical role parallelism. L1 participants did not reveal any preferentially looks towards the object antecedent, which is not in agreement with previous studies (e.g., Sauermann, Gagarina 2017, Smyth 1994, Schumacher et al 2016. Whereas L2 participants looked more frequently towards the object antecedent than to the subject antecedent.…”
Section: Discussioncontrasting
confidence: 83%
“…The current study evaluated whether the grammatical role hypothesis (e.g., Smyth 1994) holds for the resolution of the German accusative object pronoun ihn 'him'. Previous studies showed an impact of grammatical role parallelism on subject pronoun resolution (e.g., Sauermann, Gagarina 2017, Schumacher et al 2016. The results of Experiments 1a and 2a indicate that after encountering the object pronoun, L1 and L2 German speakers did not show a rapid use of grammatical role parallelism.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The influence of subject-hood and order-of-mention on pronoun interpretation are only tendencies, and other things can influence pronoun interpretation such that the grammatical subject / first referent is not the preferred antecedent. For instance, when the pronoun is an accusative pronoun (e.g., him or her), grammatical objects are preferred as antecedents (Chambers & Smyth, 1998;Sauermann & Gagarina, 2017). The previously mentioned effects are all structural, that is, they involve the structure of sentences in one way or another.…”
mentioning
confidence: 99%
“…Importantly, in Schumacher's approach, the relevance of thematic role for pronoun resolution does not completely rule out the contribution of other factors such as grammatical role. Indeed, grammatical role may be an important factor when the grammatical role of the pronoun is also considered, where grammatical role parallelism may exert an influence (Sauermann & Gagarina, 2017). Rather, it is proposed that these factors form prominence hierarchies which interact to determine the appropriate referent.…”
Section: Personal and Demonstrative Pronouns In Germanmentioning
confidence: 99%